Leadership and Overtime Incentives: Mental Health and Gen Z Job Satisfaction - Masruroh, Rina; Mariana, Lia; Irawan, Nico; Oktaviani, Winda (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
This study aimed to analyze the influence of empowering leadership, overtime work, and overtime incentives on the job satisfaction of Generation Z employees at Kuningan Regency, with employee mental health as a mediating variable. The research was motivated by the fluctuating employee turnover rate over the past three years and increasing challenges in managing Gen Z employees. A quantitative approach was used, employing Structural Equation Modeling (SEM) through AMOS. A total of 156 respondents were selected using purposive sampling. The results showed that empowering leadership did not significantly affect mental health, but had a direct positive effect on job satisfaction. Overtime work had a positive effect on mental health but a negative effect on job satisfaction. Overtime incentives did not significantly affect mental health, but had both direct and indirect positive effects on job satisfaction through mental health. Mental health played a significant mediating role in the relationship between overtime work and overtime incentives with job satisfaction, but not in the relationship between empowering leadership and job satisfaction. The model demonstrated a good level of fit. These findings highlighted the importance of balanced management of overtime and incentives, as well as the critical role of mental health in improving Gen Z employee satisfaction.